Accounting Treatment for Derivatives: Issues and Challenges - Tulsian, P. C.; Tripathi, Aditya Prakash (Indian Journal of Finance, 2009)
The accounting standard on financial instruments is not a simple exercise. If we take the global perspective into consideration, we find that both the US and international standard setters have written thousands of pages by way of interpretation and guidance on the standards. In US, the standard setters have brought several new standards to clarify the scope and application of the original standards. Almost a decade after implementation, the standard is still every accountant’s nightmare. India has been going with an antiquated AS 13 for years after almost the entire world has implemented standards parallel to IAS 39. AS 30 has been given substantial time for implementation - it is supposed to be applied for financial year 2009-10 on a recommendatory basis, and 2011-12 on a mandatory basis to make it more amicable and user-friendly. The recent direction of the Institute of Chartered Accountants of India (ICAI), requiring companies to provide for losses arising from the measurement of derivatives at market value, has left many questions folded. Furthermore, companies are less likely to want to adopt accounting rules that require higher disclosure, or the application of which results in presentation of lower profit or assets. The present paper makes an attempt to unravel the issues relating to Accounting, Auditing&Taxation perspective of Derivatives in the light of As-30. It also tries to clearly explain the challenges involved in the implementation of AS-30.